Effect of Butyric Acid on Carcass Characteristics and Serum Biochemical Parameters in Broiler Chicken - Nataraja, D.; Malathi, V.; Jayanaik; Sreedhara, J. N. (International Journal of Livestock Research, 2020)
A biological experiment was conducted to evaluate the effect of butyric acid on carcass characteristics and serum biochemical parameters in broiler chicken. The experiment consisted of 4 experimental diets. 600 day-old broiler chicks were randomly assigned to one of the four dietary treatments containing 150 chicks each: T1 (basal diet), T2 (basal diet + 0.1 % butyric acid), T3 (basal diet + 0.2 % butyric acid) and T4 (basal diet + 0.4 % butyric acid). Dressing per cent, abdominal fat per cent, relative weights of liver and spleen were found to be unaffected by butyric acid supplementation. Whereas, increase in the relative weights of heart at 0.1 per cent and reduced weight of gizzard at 0.1 and 0.2 per cent levels of butyric acid supplementation was recorded at the end of the trail. Significantly higher levels of albumin and uric acid on day 42 and glucose on day 21 was recorded in butyric acid supplemented groups. Decreased levels of globulin on day 42, cholesterol and creatinine levels during both 21 and 42nd days was noted. Serum levels of ALT and ALP was lower at the end of trail in butyric acid supplemented groups.